Serum Neutrophil Gelatinase Associated Lipocalin (NGAL) Outperforms Serum Creatinine in Detecting Sepsis-Induced Acute Kidney Injury, Experiments on Bilateral Nephrectomy and Bilateral Ureter Obstruction Mouse Models. Issue 5 (May 2016) - Leelahavanichkul, Asada; Somparn, Poorichaya; Issara-Amphorn, Jiraphorn; Eiam-ong, Somchai; Avihingsanon, Yingyos; Hirankarn, Nattiya; Srisawat, Nattachai
Abstract : ABSTRACT: Serum neutrophil gelatinase associated lipocalin (sNGAL), a promising acute kidney injury (AKI) biomarker produced by renal and non-renal tissues, might be affected by sepsis. We evaluated sNGAL in zero glomerular filtration rate models [bilateral ureter obstruction (BUO) and bilateral nephrectomy (BiNx)] with subsequent cecal ligation and puncture (CLP)-induced sepsis in 6 to 8-week-old ICR mice. We found that sNGAL increased earlier than serum creatinine (Scr) in BiNx/BUO with and without CLP. The earliest time-point of increased sNGAL in BiNx+CLP was 1 h after surgery. Scr, but not sNGAL, was lower at 18 h after BiNx/BUO+CLP compared with BiNx/BUO alone. Compared with BUO, BiNx had higher, and equal sNGAL at 1 to 18 h and 36 h, respectively. Additionally, similar NGAL expression in internal organs (heart, lung, liver, and spleen) and survival rates indicated the comparable severity of BiNx and BUO. Serum interleukin (IL)-6 was increased and correlated with sNGAL in BiNx/BUO with and without sepsis. In summary, we demonstrated: sNGAL is an early AKI biomarker, which is not affected by sepsis; sNGAL is mainly produced by extrarenal sources as demonstrated by the comparable sNGAL in BiNx and BUO; the saturation of renal NGAL re-absorption in BUO is demonstrated by lower sNGAL in BUO at 1 to 18 h, but not at 36 h when compared with BiNx; and a correlation of sNGAL and IL-6 implied sNGAL is a good sepsis prognostic biomarker. Therefore, sNGAL is a more beneficial sepsis-AKI biomarker than Scr.